Joint Effect of CFH and ARMS2/HTRA1 Polymorphisms on Neovascular Age-Related Macular Degeneration in Chinese Population - Kai Fang; Pei Gao; Jun Tian; Xueying Qin; Wenzhen Yu; Juan Li; Qing Chen; Lvzhen Huang; Dafang Chen; Yonghua Hu; Xiaoxin Li (Journal of Ophthalmology)
Purpose. The etiology of neovascular age-related macular degeneration (nAMD) cannot be completely explained by identified environmental risk factors or single-locus gene variants. This study was to explore the potential interactions among gene variants on nAMD in Chinese population. Methods. 43 SNPs located in different genes were genotyped in 932 Chinese individuals (464 nAMD patients and 468 controls). We explored the potential interactions among gene variants using generalized multifactor dimensionality reduction (GMDR) algorithm and the method to measure the departure from the additivity model. Results. The joint effect that involved CFH rs1061170 and HTRA1 rs3793917 was shown statistically significant (P < 0.001) with the highest cross-validation consistency (10/10) and the best testing balanced accuracy (64.50%). In addition, based on the method to measure the departure from the additivity model, the synergy index (S) was 2.63 (1.09–6.38) and the attributable proportion due to interaction (AP) was 55.7% (21.4%–89.9%), which suggested that a common pathway may exist for these genes for nAMD. Those who carried CC for rs3793917 and TC/CC for rs1061170 were at the highest risk of nAMD (OR: 9.76, 95% CI: 4.65–20.51). Conclusions. Evidence that the joint effect that involved CFH and ARMS2/HTRA1 may contribute to the risk of neovascular AMD in Chinese population was obtained.